1984
DOI: 10.1128/jb.158.1.347-350.1984
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of dihydrouracil in Rhodosporidium toruloides

Abstract: Previous studies, including those done with a similar species, have indicated that dihydrouracil is formed by the breakdown of uracil and is degraded into N-carbamyl-beta-alanine. (Fink et al., J. Biol. Chem. 201:349-355, 1953; S. R. Vilks and M. Y. Vitols, Mikrobiologiya 42:567-583, 1973; O. A. Milstein and M. L. Bekker, J. Bacteriol. 127:1-6, 1976). In the present work the conversion of dihydrouracil to uracil is studied in Rhodosporidium toruloides, and the growth characteristics of mutants that have lost t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Dihydrouracil and uracil participate in pyrimidine metabolism pathway (belong to ''nucleotide metabolism''), where 5,6-dihydrouracil and NADP+ are catalyzed by dihydropyrimidine dehydrogenase (DPD) to form uracil and NADPH+H+ [14,27]. They are also co-mentioned in many PubMed Abstracts such as [28,29,30,31,32,33,34,35,36,37]. Another two interactive compounds -dihydrouracil and dihydrothymine share a very similar structure, the only difference is that dihydrothymine has a methyl at the 5th position of the hexatomic ring while dihydrouracil has not [38].…”
Section: Evaluation Results By the 5-fold Cross-validationmentioning
confidence: 99%
“…Dihydrouracil and uracil participate in pyrimidine metabolism pathway (belong to ''nucleotide metabolism''), where 5,6-dihydrouracil and NADP+ are catalyzed by dihydropyrimidine dehydrogenase (DPD) to form uracil and NADPH+H+ [14,27]. They are also co-mentioned in many PubMed Abstracts such as [28,29,30,31,32,33,34,35,36,37]. Another two interactive compounds -dihydrouracil and dihydrothymine share a very similar structure, the only difference is that dihydrothymine has a methyl at the 5th position of the hexatomic ring while dihydrouracil has not [38].…”
Section: Evaluation Results By the 5-fold Cross-validationmentioning
confidence: 99%
“…Based on our phylogenetic analysis, it is highly probable that dho genes occur in a wide range of ascomycetes and basidiomycetes (Figure 2). Before this study, DHO activity had only been reported in two publications on the yeast Rhodotorula glutinis (Davis et al 1984;Owaki et al 1986) and no structural gene for DHO had been identi ed.…”
Section: Discussionmentioning
confidence: 99%
“…In the reductive pathway for pyrimidine degradation, dihydropyrimidine dehydrogenases (DPHD) catalyse the reduction of uracil to dihydrouracil, using NAD(P)H + H + as electron donor. c. Dihydrouracil oxidase (DHO), which has only been described in Rhodotorula glutinis (Davis et al 1984;Owaki et al 1986), catalyses oxidation of dihydrouracil with molecular oxygen and forms hydrogen peroxide. Sequence identi ers corresponding to the phyla Basidiomycota, Ascomycota and Mucoromycota are indicated in color.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations